Analisis Pengaruh Indeks Harga Konsumen Bulanan Terhadap Inflasi Makanan Bulanan melalui Metode Analisis Regresis Sederhana - Qathrunnada Salsabila; Nafisah Itsna Hasni (CiDEA Journal, 2023)
Economic stability created price stability, because a stable economy could result in low or affordable costs for the community. One indication of economic stability was inflation. Meanwhile, the Consumer Price Index was an important indicator of the financial market and was a general indicator of the level of inflation in Indonesia. For this reason, this research aimed to analyze the influence of the monthly consumer price index on monthly food inflation in Cilacap Regency. The data used in the research came from the Cilacap Regency Central Statistics Agency, which was then analyzed using a simple regression analysis method. The results of the analysis showed that there was no significant influence between the monthly consumer price index and monthly inflation. This was because the CPI was one of the indicators was used to measure the level of inflation. Changes in the CPI over time described the rate of increase (inflation) or rate of decline (deflation) of goods and services.